Diversification and selection pattern of CYP6B genes in Japanese Papilio butterflies and their association with host plant spectra - Sato, Ai; Okamura, Yu; Murakami, Masashi (PeerJ, 2020)
Herbivorous insects are thought to have evolved counteradaptations to conquer chemical defenses in their host plants in a stepwise co-evolutionary process. Papilio butterflies use CYP6B gene family members to metabolize furanocoumarins in their Rutaceae or Apiaceae host plants. CYP6Bs have functionally diverged among Papilio species to be able to metabolite diverse types of furanocoumarins in their host plants. In this study, we examined the diversification and selection patterns of CYP6B among nine Papilio species in Japan (eight Rutaceae specialists and one Apiaceae specialist) and their association with host plant spectra and furanocoumarin profiles. We compared host plant spectrum of eight Rutaceae feeding Papilio species and also performed a furanocoumarin profiling of their host plants. In addition, we reconstructed CYP6B gene phylogeny and performed selection analysis based on the transcriptome data of those nine Papilio species. Among Rutaceae-feeding Papilio species, host plant spectrum differences were correlated with their furanocoumarin profiles. However, all tested Papilio species had similar duplicated sets of CYP6B, with no apparent lineage-specific or host plant-specific pattern of CYP6B diversification. Selection analysis showed a signature of positive selection on a CYP6B branch. The positively selected sites located at predicted substrate recognition sites and we also found that these CYP6B genes were observed only in Rutaceae-feeding species. These findings indicate that most CYP6B diversification occurred in ancestral species of these Papilio species, possibly in association with specific host plant chemical defenses and subsequent gene loss due to host specialization. These processes would have shaped the complex diversification patterns of the CYP6B gene family in Papilio butterflies. Our results also show potentially important CYP6B clades among Papilio species which likely to have diverged functions and associated with host plant phytochemicals in ancestral Papilio species.
Keywords: Plant; Counteradaptation; Secondary metabolites; Herbivorous insect; Papilio